THE POTENTIAL OF CIRCULARITY IN THE DEVELOPMENT OF THE UPSTREAM-DOWNSTREAM COFFEE AGROINDUSTRY TO FOSTER A GREEN ECONOMY AND ENHANCE CLIMATE RESILIENCE (Jurnal Teknologi Industri Pertanian, 2026)
This study evaluates the Arabica coffee production system at Koperasi Ketakasi using a circular economy approach to identify potential efficiency gains and waste reduction. The system remains linear mainly, as shown by a Material Circularity Indicator (MCI) of 0.227 and a Linear Flow Index (LFI) of 0.863. The drying stage causes the most significant waste, consuming 92% of production time, with unutilized solid and liquid waste. Waste causes were analyzed using a 6M fishbone diagram (man, method, machine, material, environment, management). Circular opportunities include converting waste into compost, liquid fertilizer, briquettes, animal feed, and defective beans. Based on the 9R framework, reduce, reuse, and repurpose strategies are feasible for phased implementation, offering economic benefits (Net B/C > 1; payback < 0.5 years). These strategies can improve production efficiency, reduce environmental impact, and support the sustainability of the cooperative and coffee farming community.Keywords: circular economy, coffee agroindustry, green economy, Ketakasi Cooperative, resilience